STATISTICAL ANALYSIS FACTORS AFFECTING OF RICE PRODUCTION IN PAKISTAN: A CASE STUDY OF DISTRICTS JAFFARABAD AND GUJRANWALA - Meerullah; Rahmat Ali; Mutiurrehman; Mohammad Awais; Adnan Saeed (International Journal of Contemporary Issues in Social Sciences, 2024)
The article identifies the primary factor influencing rice output in the Baluchistan districts of Jaffarabad and Gujranwala in the Punjab between 1989 and 2008. Secondary data was used, including information on cropping systems, input usage, management strategies, and other pertinent subjects. The production system was found to employ conventional techniques, which results in poor production relative to the potential yield. Two major factors that impacted production were a lack of rain and a lack of water, and 43.7 percent of producers in the research region employed the rice variety. The rice farmers applied just 37.5kg of phosphorus per acre of artificial fertilizer, with little variation in their usage. The rice-planted area in the study region had a loss of 0.04%.54.5% of growers blamed the high cost of chemical fertilizer for the decrease in rice average, while 25% blamed the scarcity of high yielding variety seed. The objectives of this study is to find out the factors affecting on rice production one variety of rice taken from two districts of Pakistan of study purpose.